4 > x
step by step explanation:
13 > 3x + 1
-1 -1
12 > 3x
/3 /3
4 > x
Yes that is correct ma dude
Answer:
f(-4)= 24
Step-by-step explanation:
-4(-4)+8 We need to multiply -4 and -4 and a negative times a negative is a positive.
16+8 Now it's easy math and we just add them
This gives us 24.
Answer:
(x-2)/(2x+8)
Step-by-step explanation:
The first step to solve this expression is to use a² - 2a b + b² = (a - b)² to factor the expression
Factor out 2 from the expression
Write 2x as a difference
Factor out x from the expression
Factor out -2 from the expression
Factor out x + 4 from the expression
Reduce the fraction with x - 2
Finally,, distribute 2 through the parenthesis to find your answer
This means that the correct answer to your question is (x-2)/(2x+8)
X=1 & Y=12
X=2 & Y=20
X=3 & Y=30